SCARS IN SILENCE: GENDERED NARRATIVES OF THE ASSAM AGITATION AND INSURGENCY IN CONTEMPORARY ASSAMESE LITERATURE - Singha, Aradhana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The period of Assam Agitation (1979-1985) was a period of severe socio-political unrest that had a deep emotional and physical impact on the vulnerable and the marginalised. This paper will investigate the representation of Assamese women in contemporary Assamese literature, especially in the works of Arupa Patangia Kalita and Aruni Kashyap. It will understand their work through the theoretical lens of feminist literary criticism, subaltern theory and trauma studies. Through this lens, the focus is on understanding the representation of women as grieving mothers, survivors of violence and silent witnesses. This period was profound with emotional anguish and grief. The authors in discussion often analyses the political implications of grief on women. As these women navigate trauma, loss, anguish, abuse, relocation and grief, their stories are used as a counter to official narratives where their participation in pain is often absent. Their literature gives a voice to the experiences of these women giving a profound and intimate documentation of their suffering.